On the conharmonic and concircular curvature tensors of almost C($λ $) Manifolds - akbar, Ali; Sarkar, Avijit (International Journal of Advanced Mathematical Sciences, 2013)
The object of the present paper is to characterize certain curvature conditions on conharmonic and concircular curvature tensors on almost C($λ $) manifolds. In this paper we study conharmonically flat, $ξ $-conharmonically flat, concircularly flat and $ξ $-concircularly flat almost C($λ $) manifolds.